Transfer. Psychoanalysis integration and Logotherapy - Ovejas, Patricia (2011)
The present article analyzes the integration of Psychoanalysis contributions, Logotherapy and Philosophy in the clinical area. An exhaustive bibliographical review was carried out adopting a critical perspective, and as primary sources, Freud, Frankl, several philosophers and psychoanalyst authors as well as existentialists’ works were analized. The main conclusions are that since a particular idea of a man and going towards the transfer concept, it is revealed that the integration among Psychoanalysis, Logotherapy and Philosophy is not only possible but vitally necessary. On the other hand, the man, so different in their essence, will need multiple approaches and integrators to reach mental health.